2016
DOI: 10.1002/ejic.201600335
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazone‐Ligand‐Based Homodinuclear Lanthanide Complexes: Synthesis, Structure, and Magnetism

Abstract: A series of dinuclear lanthanide complexes, [Dy2(LH)2(µ2‐Piv‐κ2O,O′)2(NO3‐κ2O,O′)2] (1), [Tb2(LH)2(µ2‐Piv‐κ2O,O′)2(NO3‐κ2O,O′)2] (2), [Gd2(LH)2(µ2‐Piv‐κ2O,O′)2(NO3‐κ2O,O′)2] (3), and [Ho2(LH)2(µ2‐Piv‐κ2O,O′)2(NO3‐κ2O,O′)2] (4) have been synthesized by the reaction of Ln(NO3)3·nH2O with the multidentate hydrazone‐based Schiff‐base ligand, N′‐(2‐hydroxy‐3‐methoxybenzylidene)acetohydrazide (LH2) in the presence of pivalic acid. X‐ray crystallography data reveals that 1–4 are isostructural, neutral, and contain tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 97 publications
1
30
0
Order By: Relevance
“…Four oxygen atoms (O1, O2, O4, O6) bind only one Dy III ion (μ 1 mode) and four oxygen atoms (O3, O3a, O5, O5a) bind two Dy III ions (μ 2 mode; Figure and Table S1 in the Supporting Information). From the magnetic point of view, this last coordination mode is expected to transmit a sizeable magnetic interaction between the Dy III ions , , . The Dy III ion presents a muffin‐like coordination polyhedron ( C s ) (Figure , Table S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Four oxygen atoms (O1, O2, O4, O6) bind only one Dy III ion (μ 1 mode) and four oxygen atoms (O3, O3a, O5, O5a) bind two Dy III ions (μ 2 mode; Figure and Table S1 in the Supporting Information). From the magnetic point of view, this last coordination mode is expected to transmit a sizeable magnetic interaction between the Dy III ions , , . The Dy III ion presents a muffin‐like coordination polyhedron ( C s ) (Figure , Table S2 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We have been involved in the design and utilization of various types of ligand families for the preparation of 3d/4f, and 4f,,, complexes. From our experience,, and those of others we have observed that flexible ligands that have multiple options to bind to a metal ion are often suitable to generate polynuclear complexes. Among the ligands that we have investigated, aroyl hydrazone ligands have been found to possess the following beneficial features.…”
Section: Resultsmentioning
confidence: 99%
“…We have been utilizing multidentate hydrazone ligands, for some time, to assemble lanthanide complexes . In this context, we wished to explore a o ‐vanillin‐supported multidentate ligand, N′ ‐(2‐hydroxy‐3‐methoxy‐5‐nitrobenzylidene)‐2‐(hydroxyamino) propanehydrazide (H 3 L) to prepare dinuclear Ln III complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[14] We have been utilizing multidentate hydrazone ligands, for some time, to assemble lanthanide complexes. [29][30][31] In this context, we wished to explore a o-vanillin-supported multidentate ligand, N′-(2-hydroxy-3-methoxy-5-nitrobenzylidene)-2-(hydroxyamino) propanehydrazide (H 3 L) to prepare dinuclear Ln III complexes. Based on our previous understanding of such ligand systems we intuited that keto-enol tautomerism would allow H 3 L to be present in an enol form and when de-protonated the enolate oxygen can be profitably used to bridge two lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%